Development of an Automated Self-assessment of Fall Risk Questionnaire for Hospitalized Patients. Issue 1 (January 2016) - Sitzer, Verna
Abstract : Falls in hospital settings continue to challenge health care providers. Multifactorial interventions aim to reduce falls but rarely involve the patient as an active participant. A patient self-assessment of fall risk questionnaire was customized in the hospital's computer-based, television-equipped, interactive patient care system. Designed to engage patients in determining their risk for falling, the questionnaire is a reliable and valid means for patients and nurses to assess risk of falls. Abstract : Supplemental Digital Content is Available in the Text.